Comparing the effects of tofogliflozin and pioglitazone in non-alcoholic fatty liver disease patients with type 2 diabetes mellitus (ToPiND study): a randomized prospective open-label controlled trial. Issue 1 (16th February 2021) - Yoneda, Masato; Honda, Yasushi; Ogawa, Yuji; Kessoku, Takaomi; Kobayashi, Takashi; Imajo, Kento; Ozaki, Anna; Nogami, Asako; Taguri, Masataka; Yamanaka, Takeharu; Kirikoshi, Hiroyuki; Iwasaki, Tomoyuki; et al.
Abstract : Introduction: The treatment of diabetes has a significant impact on the pathogenesis of non-alcoholic fatty liver disease (NAFLD). We compared the effectiveness of tofogliflozin, a selective sodium-glucose cotransporter 2 inhibitor, and pioglitazone for the treatment of NAFLD patients with type 2 diabetes mellitus. Research design and methods: This open-label, prospective, single-center, randomized clinical trial recruited NAFLD patients with type 2 diabetes mellitus and a hepatic fat fraction of at least 10% as assessed based on the MRI-proton density fat fraction (MRI-PDFF). Eligible patients were stratified according to hemoglobin A1c (HbA1c), alanine transaminase, and MRI-PDFF levels and randomly assigned (1:1) to receive either 20 mg tofogliflozin or 15–30 mg pioglitazone, orally, once daily for 24 weeks. The primary endpoint was an absolute change in MRI-PDFF at 24 weeks. Efficacy and safety was assessed in all treated patients. This trial was registered in the Japan Registry of Clinical Trials. Results: Overall, 40 eligible patients were randomly assigned to receive tofogliflozin (n=21) or pioglitazone (n=19). Changes in hepatic steatosis after 24 weeks of treatment were evaluated by MRI-PDFF, which showed a significant decrease in both groups (−7.54% (p<0.0001) and −4.12% (p=0.0042) in the pioglitazone and tofogliflozin groups, respectively). Compared with baseline, the body weight decreased by 2.83±2.86 kg (−3.6%, p=0.0443) in the tofogliflozin group and increased by 1.39±2.62 kg (1.7%, p=0.0002) in the pioglitazone group after 24 weeks. No life-threatening events or treatment-related deaths occurred. Conclusions: Tofogliflozin was well tolerated, and it reduced the MRI-PDFF levels in NAFLD patients with type 2 diabetes mellitus. Trial registration number: jRCTs031180159.